INCREASING SALES OF STUDENT ENTREPRENEURSHIP POST-COVID-19 THROUGH E-COMMERCE-BASED TECHNOLOGY AS A MARKETING MEDIA - Levia Inggrit Sayekti (Sean Institute, 2023)
Entrepreneurs must have competitiveness to survive, Salah one strategy to increase competitiveness by using the right marketing media by combining offline and online marketing media. E-commerce has a positive and significant influence on improving business performance (M. Z. Abidin, 2016). The purpose of this study is to provide education to entrepreneurial students at Lamongan Islamic University who are the samples in this study, to be able to optimize the use of E-Commerce media as a marketing medium. This research uses descriptive qualitative methods by utilizing secondary data derived from key informants, literature books, articles, and homepages to access the latest data and information related to various analyzes of increasing sales by optimizing the use of information technology based on E-commerce. This research results that the use of information technology requires strong support from all parties. Therefore it is necessary to optimize several aspects which in this case are the variables discussed in the study. Socialization and education, resources in the form of the availability of information technology in the form of applications and materials used as support in marketing through E-Commerce. The results of the study stated that 100% of entrepreneurs who are members of the Unisla entrepreneurial community under the auspices of the Business Incubator Center at the Islamic University of Lamongan have used E-Commerce, namely social media Instagram and Marketplcae Tiktok and Shopee. It is hoped that entrepreneurial students can do marketing optimally and understand in the procedure for operating social media and marketplace so it's not just about owning. Socialization and education need to be carried out continuously for entrepreneurs to invigorate their trading spirit and be able to make better use of information technology as a marketing medium after the covid19 pandemic (Baker and Judge, 2020).